Economic Integration and Similarity in Trade Structures - Lucia Tajoli; Lucia De Benedictis (Fondazione Eni Enrico Mattei (FEEM), 2006)
In this paper we look at the similarity of trade structures in an integrating area. In particular, we analyse the export flows toward the EU market of four of the so-called accession countries of Central and Eastern Europe by comparing them to those of the pre-2004 members of the European Union (EU15). From a methodological point of view, we evaluate the appropriateness of different classes of similarity indices - correlation indices and distance metrics - opting for the use of the Bray-Curtis semi-metric to assess changes in the trade similarity. We examine its evolution over time - from 1989 to 2001 - considering both self-similarity (how the export composition of a CEEC has changed with respect to the beginning of the transition process) and EU-similarity (if and how the export composition of a CEEC has changed with respect to the EU15 export composition). Finally, we use EU-similarity matrices to test if the dynamics of sectoral distribution of total exports of Poland, Hungary, Romania, and Bulgaria to the EU is related to the role acquired by processed trade in the 1990s. Using a nonparametric Mantel test we give evidence that: (1) processed trade is crucial in explaining changes in the overall structure of exports of transition countries, and (2) that greater economic integration in terms of trade flows and processing trade does not always lead to greater export similarity between the CEECs and the EU15 member States.
Keywords: F3; F42; 330; EU; CEECs; Transition; Similarity; Nonparametrics; Außenhandelsstruktur; Handelsregionalismus; Nichtparametrisches Verfahren; EU-Staaten; Osteuropa; EU-Staaten (Osteuropa)